Facile Synthesis and Characterization of Lanthanum (III) Oxychloride Nanoparticles using a Natural Polymeric Matrix - Khorsand, Z.A.; Abd Majid, Wan Haliza; Darroudi, M. (Elsevier, 2012)
Plate-shape lanthanum oxychloride nanoparticles (LaOCl-NPs) were synthesized via a facile sol-gel method in gelatin media. The LaOCl-NPs were characterized by a number of techniques, including X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR), Auger electron spectroscopy (AES), and high-magnification transmission electron microscopy (TEM). The LaOCl-NPs calcined at different temperatures exhibited a tetragonal structure. The influence of the calcination temperature on the morphology of LaOCl-NPs was also investigated. The TEM shows that the particles were grown in plate shape. The Auger result proved the purity of the final product. The results demonstrated that gelatin is an interesting material that can be used as a stabilizer in the sol-gel technique for preparing LaOCl-NPs. Â© 2012 Elsevier B.V. All rights reserved.